REVIEW OF BEHAVIORISM THEORY ON NGENGER WAY OF LIFE AMONG SANTRI - Ishomudin, Muhammad; Haryanto, Budi; Astutik, Anita Puji (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to analyze the way of life of ngenger among santri (pesantren students) from a behavioristic point of view at Fadllillah Waru Sidoarjo Islamic Boarding School. This study applies a phenomenological qualitative approach. The object of this study is the students who ngenger in the pesantren (Islamic boarding schools, in some conditions, may be closer to an Islamic Monastery). Data were collected by observation and interview techniques. Data analysis using interactive model analysis techniques from Miles and Huberman. The results of the study explained that students who